Pengaruh Guided Discovery Learning Terhadap Hasil Belajar Matematika Siswa Kelas IV SD Inpres Bontomanai Kota Makassar - Muh. Fahrul Nur; Muhammad v; Wahyuddin Wahyuddin (Journal on Education, 2023)
The Effect of Guided Discovery Learning on the Mathematics Learning Outcomes of Class IV Students of SD Inpres Bontomanai, Makassar City. Thesis. Department of Elementary School Teacher Education, Faculty of Teacher Training and Education, University of Muhammadiyah Makassar. Supervised by Muhammad Muzaini and Wahyuddin. This study aims to describe the effect of guided discovery learning on the mathematics learning outcomes of fourth grade students at SD Inpres Bontomanai, Makassar City. This type of research is a quasi-experimental design research that aims to determine the effect of applying the guided discovery learning model to the mathematics learning outcomes of fourth grade students at SD Inpres Bontomanai, Makassar City. The sample in this study were 24 students from the experimental class and 27 students from the control class. Data collection techniques were carried out using learning outcomes tests in the form of pretest and posttest. Data analysis techniques in this study are descriptive data analysis techniques and inferential data analysis.The results showed that there was an increase in the learning outcomes of fourth grade students at SD Inpres Bontomanai with the application of the guided discovery learning model. This can be proven based on the results of the Independent-Samples T Test results obtained by the value of Sig. (2-tailed) of 0.00, because Asymp. Sig. (2-tailed) < 0.05 then Ha is accepted and Ho is rejected so it can be concluded that there is a significant difference between the experimental class and the control class before learning where the control class has an average value of 87.50 much higher than the control class with the average value is 67.96. So it can be concluded that there is an influence of the guided discovery learning model on the mathematics learning outcomes of fourth grade students at SD Inpres Bontomanai Makassar City